Pengembangan Buku Saku Keanekaragaman Hayati Berbasis Tumbuhan Obat di Kecamatan Kampar Kiri Hulu Kabupaten Kampar - pazila, rezka; darmadi; nursal (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
Biodiversity refers to the variety of life that encompasses all living organisms on Earth, ranging from genetic, species, to ecosystem levels. Education is a vital aspect of human life. In simple terms, education is a human effort to develop individual potential in accordance with cultural norms and the surrounding environment. Understanding biodiversity is essential in biology learning as it helps students recognize the natural potential of their surroundings. This research aims to design a biodiversity pocketbook based on medicinal plants found in Kampar Kiri Hulu District, Kampar Regency, as a contextual and engaging biology learning medium for high school students. The research was conducted in two stages: identification of medicinal plant species through field surveys and interviews with local communities, and the development of the pocketbook using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The identification results revealed 59 medicinal plant species from 33 families, with the Zingiberaceae family being the most dominant. These plants are traditionally processed by methods such as boiling, pounding, and topical application, and are used to treat various common to internal diseases. The pocketbook includes detailed descriptions, original photographs, classifications, benefits, and usage methods of the medicinal plants. Validation by media and material experts indicated that the pocketbook is valid in terms of content structure, language, and graphic design. This pocketbook can be used in Phase E of the Merdeka Curriculum, especially for species-level biodiversity material. Besides serving as a learning resource, this pocketbook also functions as documentation of local knowledge that has been passed down orally and not yet systematically recorded.